Toward a ‘Masonic musicology’ Some theoretical issues on the study of Music in relation to Freemasonry - Vergauwen, David (2018)
The paradigm called ‘New Historicism’ and its many spin-offs like ‘New Musicology’, proclaims that an art historian should no longer limit itself to solely the study of an artwork, but should instead focus on its historical and sociological “context”. By means of a new tool that we shall label “Masonic musicology” will argue that the logic used by New Musicologists and of even Ethnomusicologists also applies to the study of music in relation to freemasonry. Studying a composer’s involvement with freemasonry, can lead to inspiring new interpretations of a composer’s work.